PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY TERHADAP PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK - Anggela, Elsa (Departemen Matematika, 2024)
Improving students' understanding of mathematical concepts is one of the main goals of education. This is the case in class XI at SMAN 1 Lintau Buo which still has low scores, which is most likely due to the fact that the learning model used is less varied. Therefore, class XI F5 was used as the experimental group and used cooperative learning approach based on Two Stay Two Stray (TSTS) paradigm, while class XI F3 used conventional model. This research is a quasi-experimental with posttest-only control group. Random selection of students from class XI at SMAN 1 Lintau Buo was used to make the research population (random sampling). Data analysis showed a P-value =0.004, which means the null hypothesis (H0) is rejected. Based on this result, it appears that the TSTS model outperforms the conventional model approach.Keywords– Cooperative learning model, Two Stay Two Stray, Understanding Mathematical Concept.